PROSTATA SARATONI KASALLIKINI SUN’IY INTELLEKTNING LINEAR REGRESSION ALGORITHM YORDAMIDA 2050-YILLARGACHA O‘SISHINI BASHORATLASH - Sh.Nazirova, E.; Azimjonov, J.; Madolimov, F. (SCIENCE and SOCIETY, 2024)
Using the linear regression algorithms of deep learning and machine learning methods, when we took the population of 1989-2023, i.e. 34 years, into our model, the population in 1989 was 5223704000. By 2050, it was predicted to be 10340540799. The number of deaths from prostate cancer was 232,999 in 1990, and 715,804 by 2050 were predicted by our linear regression algorithm model. Through the Lienar algorithm model, we need to determine the increase and decrease of data using statistical data in the future, and based on this data, we can prevent the production of food products for the population, prevent prophylactic measures for prostate cancer, and ensure human health.